Interleukin 7 receptor functions by recruiting the tyrosine kinase p59fyn through a segment of its cytoplasmic tail. - Venkitaraman, A R (1992)
Engagement of the cell surface receptor for interleukin 7 (IL-7R) provokes protein tyrosine phosphorylation, although the receptor lacks a kinase catalytic domain in its cytoplasmic tail. The molecular basis of this response is not known. Here we report that the IL-7R functions by recruiting p59fyn, an intracellular tyrosine kinase of the src family. Treatment of pre-B cells with IL-7 causes an enhancement of the catalytic activity of p59fyn, but not of the related kinase p62yes. IL-7-dependent stimulation of the enzyme phosphatidylinositol 3-kinase, a tyrosine kinase substrate, provides further evidence suggestive of p59fyn activation. We demonstrate that p59fyn forms part of a protein complex with the IL-7R. A chimeric receptor comprising the CD8 extracellular domain and the IL-7R cytoplasmic tail (CD8/IL-7R) recruits tyrosine kinase activity in transfected myeloma cells, and p59fyn can be detected in association with it by immunoprecipitation and immunoblotting. Conversely, p59fyn immunoprecipitates contain the phosphorylated CD8/IL-7R. We have identified a segment of the IL-7R cytoplasmic tail which mediates p59fyn recruitment: a truncated CD8/IL-7R containing only this segment recruits tyrosine kinase activity, associates with p59fyn, and activates phosphatidylinositol 3-kinase. Interestingly, this segment contains no tyrosine residues, although it is the phosphotyrosine-binding src homology domains of p59fyn and phosphatidylinositol 3-kinase which mediate their association with many growth factor receptors. Thus our results suggest that an unusual interaction links IL-7R to these two important signaling pathways.